Volume 2B: 44th Design Automation Conference 2018
DOI: 10.1115/detc2018-86183
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Field Test Results From a Photovoltaic Electrodialysis Brackish Water Desalination System in Rural India

Abstract: Brackish water desalination is crucial to meet basic drinking water needs in rural India. Solar photovoltaic powered electrodialysis (PV-ED) has been justified as a more cost-effective solution than the current dominant reverse osmosis approach for off-grid systems. This paper presents preliminary results from an ongoing field pilot of a village-scale PV-ED system in Chelluru, which is a small village in South India. System performance is compared to predictions of a PV-ED parametric model of local solar irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The membrane technology has played an important role in desalination due to their effectiveness, low energy consumption and cost than thermal desalination [3]. The most common membrane technology in brackish water desalination is reverse osmosis (RO), with 60 -90% of the market share depending on location [4], [5]. Electrodialysis (ED) is gaining attention of researchers, despite the fact that electrodialysis has possessed only 4% of total installed desalination capacity far behind the RO technology which has possessed 64% [3], [6], due to the high recovery of water, less sensitivity to the change in feed water quality and lower specific energy consumption of electrodialysis (ED) process for brackish groundwater desalination compare to the pressure intensive RO process.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane technology has played an important role in desalination due to their effectiveness, low energy consumption and cost than thermal desalination [3]. The most common membrane technology in brackish water desalination is reverse osmosis (RO), with 60 -90% of the market share depending on location [4], [5]. Electrodialysis (ED) is gaining attention of researchers, despite the fact that electrodialysis has possessed only 4% of total installed desalination capacity far behind the RO technology which has possessed 64% [3], [6], due to the high recovery of water, less sensitivity to the change in feed water quality and lower specific energy consumption of electrodialysis (ED) process for brackish groundwater desalination compare to the pressure intensive RO process.…”
Section: Introductionmentioning
confidence: 99%
“…The authors adhere to publication requirements that the submitted work is original and has not been published elsewhere. The results obtained in this study favour the usage of reverse osmosis (RO) technology coupled with solar Photovoltaic (PV) units as an economically feasible alternative for brackish water desalinationObtained economic data showed that RO-PV system is an economical feasible desalination alternative [18] 2018 South India To present preliminary results from an ongoing field pilot of a village-scale PV-ED system in Chelluru, which is a small village in South India.…”
Section: Ethical Issuementioning
confidence: 74%
“…The system was designed to produce potable water cost-effectively using off-shelf components and has been operating since early 2017 with some downtime. In India, the rapid drop-off in the cost of renewable energy generation and the increased awareness of environmental sustainability have led many to explore photovoltaic-RO (PV-RO) desalination in many countries which have freshwater shortages [18]. RO systems that are powered by PV panels provide a number of benefits, including low operational costs, ease of operation, environmental friendliness, high reliability, simplicity of installation and maintenance, and suitability for use with brackish water [19].…”
Section: Figure 1 Global Solar Atlasmentioning
confidence: 99%